Bangladesh : Use of Fund Resources; Request for Emergency Assistance; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Bangladesh. (IMF Staff Country Reports; Country Report, 2008)
The fiscal impact of these policies will be significant, but donor support, improved revenue, and budget reallocations will contain domestic financing. The authorities have introduced several policies in response to the disasters. IMF staff supports the authorities' request for a purchase under the IMF's policy on emergency assistance for natural disasters. Following severe flooding, the impact of cyclone Sidr on Bangladesh has been substantial.